Brand Loyalty and Generations X, Y, Z - Rosário, Albérico Travassos; A. Casaca, Joaquim (Journal of Ecohumanism, 2025)
Given the rapid changes in the business environment companies are focusing on building a strong brand that customers can be loyal. Brand loyalty is associated with concepts such as trust, satisfaction, and commitment, which determine a customer's behaviors and attitude towards a brand. These aspects that determine brand loyalty among customers can vary from generation to generation due to various factors such as life ideologies, education, values, and tech skills. This research focuses on intergenerational customer segmentation, arguing that generations X, Y, and Z have varying attitudes towards brand loyalty. A systematic bibliometric literature review was conducted to uncover the evolutionary nuances in intergenerational brand loyalty. The review includes 78 articles published in the Scopus® database, presenting up-to-date knowledge on the topic. The bibliographic search included peer-reviewed articles published up to 2022. The findings indicate that Gen X have higher brand loyalty than Gen Y and Z since they are value-oriented, less affected by digital marketing, and are in the prime earning years of their careers. On the contrary, Gen Y is less loyal since their purchasing decisions are significantly user-generated content spread on social media. The same challenge can be experienced with Gen Z since they consider social media a critical component of their daily lives. Thus, companies looking to create loyal consumers among Gen Y and Z must work harder and understand each group's values and characteristics for better targeting.